Enhancement of Textural Quality From Daggertooth Pike Conger Fish Surimi with Sodium Tripolyphosphate and Transglutaminase Activator - Untung Trimo Laksono; Suprihatin Suprihatin; Tati Nurhayati; Muhammad Romli (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Dagger-tooth pike conger fish (Muraenesox cinerus) is known to have high edible portions and white meat, thus can be used as a surimi raw materials. However, the textural quality of this fish meat is relatively poor after washing process of surimi. This reserch was aimed to analyze the effects of TGase activator and STPP addition to increase the textural quality of surimi malong. The method used is a factorial experiment with the addition of activator TGase 0.2; 0.4 and 0.6 and STPP at concentrations 0; 0.2; 0.5 and 0.8. Parameters observed were texture profile analysis (TPA), water holding capacity (WHC) folding test, bite test, and scanning electron microscopy (SEM). The results showed that the addition of STPP and activator TGase (Ca) has significant effect on increasing the hardness, fracturability, chewiness, gumminess, bite test and the folding test. Furthermore, microscopies structure (SEM) of malong surimi showed smooth and solid surfaces.